Intervensi Latihan Tai-Chi pada Pasien Kanker yang Mengalami Fatigue - Ayu Ramadhana; Dewi Gayatri (Jurnal Keperawatan Silampari, 2023)
This study aims to analyze the tai-chi exercise intervention as an alternative to reduce fatigue in cancer patients. The method used is a systematic review using the ClinicalKey Nursing, SAGE Journal, ScienceDirect, Scopus, and SpringerLink databases. The results showed that of the 1340 articles found in the initial search, 17 were selected based on their title and abstract. Reports were read, and eight papers were selected according to predetermined criteria. The results showed a positive effect of tai-chi training in reducing fatigue in cancer patients. In conclusion, tai-chi exercise intervention can help relieve symptoms and reduce cancer-related fatigue in cancer patients. Keywords: Fatigue, Cancer Patients, Tai-chi